The promise of dynamic curriculum development models for transforming multi-level systems of theological education: a Ugandan case study. - Hovil, RJG; Carl, AE; Hendriks, HJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
The contemporary discourse on patterns of theological education suggests that diversified and integrated systems are to be encouraged, over and above more monochrome approaches. However, developing and managing such systems is a complex task. With this in mind this paper looks at the field of curriculum studies in relation to theological education, and argues that understanding curriculum in a ‘broad sense’ and the development of dynamic curriculum development models holds out great promise for the development of integrated systems of theological education. In order to earth this in praxis this approach is applied through a case study in the context of the Province of the Church of Uganda (Anglican), a church with complex multi-level patterns of theological education. A dynamic, generic curriculum development model is designed for that situation and applied to the Church to generate specific recommendations. Thus, the specific example illustrates and models the wider potential of this interdisciplinary approach.